2021
DOI: 10.3390/w13182552
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pollutants from Diffuse Pollution through the Correlation between Rainfall and Runoff Characteristics Using EMC and First Flush Analysis

Abstract: Urban stormwater runoff is an important source of pollution in receiving water bodies, mainly in cities in development. However, strategies to deal with the impacts caused by the runoff discharges, such as implementing a sustainable urban drainage system (SUDS) with optimized management, need information usually obtained through monitoring studies. Brasília is a city that has one of the highest urban growth rates in Brazil, with significant impacts on urban water resources, including diffuse pollution, generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…In contrast, the total TSS load has a significant positive correlation with the runoff peak. A positive correlation between the total TSS load and peak flow was also observed by Costa et al [31] and Szelag et al [32]. Furthermore, Egemose et al [30], Costa et al [31] and Szelag et al [32] found a significant positive correlation between total TSS load and total discharged volume and Park et al [29] showed a significant correlation between rainfall intensity and suspended solids (SS), while in this study no significant correlation between these parameters was determined.…”
Section: Correlation Analysissupporting
confidence: 73%
See 3 more Smart Citations
“…In contrast, the total TSS load has a significant positive correlation with the runoff peak. A positive correlation between the total TSS load and peak flow was also observed by Costa et al [31] and Szelag et al [32]. Furthermore, Egemose et al [30], Costa et al [31] and Szelag et al [32] found a significant positive correlation between total TSS load and total discharged volume and Park et al [29] showed a significant correlation between rainfall intensity and suspended solids (SS), while in this study no significant correlation between these parameters was determined.…”
Section: Correlation Analysissupporting
confidence: 73%
“…A positive correlation between the total TSS load and peak flow was also observed by Costa et al [31] and Szelag et al [32]. Furthermore, Egemose et al [30], Costa et al [31] and Szelag et al [32] found a significant positive correlation between total TSS load and total discharged volume and Park et al [29] showed a significant correlation between rainfall intensity and suspended solids (SS), while in this study no significant correlation between these parameters was determined. Egemose et al [30] have also shown that the total TSS load depends additionally on the catchment size, the maximum sewer length and the intensity of previous rain events.…”
Section: Correlation Analysissupporting
confidence: 73%
See 2 more Smart Citations
“…NPSP has the characteristics of randomness, extensiveness, lag, and latency, which increases the di culty of pollution prevention, detection and control (Geng et al, 2019). Therefore, we still need to strengthen the basic scienti c research to develop monitoring and control measures that are more accurate and powerful for NPSP control and to reduce the environmental impact on river basins (Costa et al, 2021). Microorganisms can adhere to pollutants entering water bodies and continue to spread to other areas via the water ow (Mushi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%